Intestinal infection with multiple parasites including Balantidium coli - Poudyal, N; Baral, R; Gyawali, N; Gurung, R; Amatya, R (Health Renaissance, 2011)
Balantidium coli is only parasitic ciliate and infrequent pathogen for human beings. The infection fundamentally affects the colon and causes variable clinical pictures, from asymptomatic to serious dysenteric forms. We present a case of diarrhea and abdominal discomfort with multiple parasites including B. coli in a patient from Sunsari, Nepal. DOI: 10.3126/hren.v9i1.4362 Health Renaissance, 2011: Vol.9 No.1:45-46